Urinary Incontinence and Overactive Bladder: A Review - Correia,Soa (2009)
Overactive bladder (OAB) and urinary incontinence (UI) are common symptoms in the adult population. In 2002, the International Continence Society provided new deﬁnitions for lower urinary tract dysfunction but the prevalence, incidence and remission estimates of OAB and UI (and its different types) vary considerably across studies. Methodological aspects, such as the sample selection and the mode of data collection, should be taken into account when comparing results. While some risk factors are well established, others, mostly evaluated in cross-sectional studies, have not been consistently associated with the occurrence of the symptoms and some caution is necessary when attempting to deﬁne causal relations. More longitudinal data are needed to conﬁrm ﬁndings from previous studies. Urinary tract dysfunctions are highly prevalent conditions among men and women and they present an important economic burden to society. Despite an important negative impact in the quality of life, urinary symptoms are often under-diagnosed and under-treated.